Impact of COVID-19 on food value chains in Uganda: Results of surveys of farmers, traders, and processors - Nabwire, Leocardia; Van Campenhout, Bjorn; Minot, Nicholas; Kabir, Razin; Vos, Rob; Narayanan, Sudha; Rice, Brendan; Aredo, Samson Dejene (International Food Policy Research Institute, 2022)
We examined the impact of COVID-19 on food value chains in Uganda, using the case of dairy and maize value chains. These two are important value chains in Uganda (in terms of contribution to food and nutrition security and export earnings), yet distinct in terms of terms of market orientation, organization, degree of vertical coordination and institutional setup.